Tadpole of Nyctimantis galeata (Anura: Hylidae: Lophyohylini), a narrow endemic casque-headed frog from Bahia, Brazil - Magalhães, Felipe De Medeiros; Marques, Ricardo; Dos Santos, Daniela Fonseca; de Magalhães, Rafael Félix; Pezzuti, Tiago Leite (Zootaxa, 2021)
Nyctimantis galeata (Pombal, Menezes, Fontes, Nunes, Rocha & Van Sluys) is a casque-headed frog member of the Lophyohylini tribe (Blotto et al. 2020), narrow-endemic to the municipality of Morro do Chapéu, Bahia state, Brazil (Pombal et al. 2012). This species was initially described as sister of Corythomantis greeningi Boulenger based on shared osteological autapomorphies within Hylidae (see Faivovich et al. 2005; Pombal et al. 2012). However, in the most recent molecular phylogenetic analysis of Lophyohylini, Blotto et al. (2020) redefined the genus Nyctimantis to accommodate species from the former genus Aparasphenodon, Argenteohyla and “Corythomantis galeata” (as initially described; Pombal et al. 2012). Currently, the genus Nyctimantis comprises seven species: N. arapapa (Pimenta, Napoli & Haddad), N. bokermanni (Pombal), N. brunoi (Miranda-Ribeiro), N. galeata, N. pomba (Assis, Santana, Silva, Quintela & Feio), N. rugiceps Boulenger, and N. siemersi (Mertens). Among these, N. arapapa (Lourenço-de-Moraes et al. 2013), N. brunoi (Wogel et al. 2006) and N. siemersi (Céspedez 2000; Cajade et al. 2010) have their tadpoles described, while oral cavity anatomy was only reported for those of N. brunoi and N. siemersi (Wogel et al. 2006; Cajade et al. 2010). Considering that larval morphology generally provides reliable information for anuran systematic and taxonomic studies (Wassersug 1980; McDiarmid & Altig 1999; Haas 2003), a formal comparison of these larvae might highlight additional non-molecular evidence that support them as congeners (Blotto et al. 2020). Herein, we describe the external morphology and oral cavity anatomy of tadpoles of N. galeata and compare it with those of related species.